Nutritional Composition and Antinutritional Factors of Five Wild Edible Fruits Grown in the Mekdela District, South of Wollo, Ethiopia - Yalew Yiblet (The Scientific World Journal)
This study was carried out to determine the mineral content and nutritional properties of five wild fruits Rhus vulgaris, Rosa abyssinica, Rhus natalensis, Euclea racemosa, and Ficus sur. The proximate composition parameters (moisture, ash, crude fiber, crude fat, and crude protein) and antinutritional factors were evaluated using methods of the Association of Official Analytical Chemists and elemental analysis using the atomic absorption spectroscopy technique. Among the five wild edible fruit species, Rhus vulgaris had the highest carbohydrate content (83.3 ± 0.28 g/100 g) and a high total energy (344.5 ± 2.21 kcal/100 g). Euclea racemosa was found to have the maximum ash content (12.8 ± 0.37 g/100 g), protein content (3.22 ± 0.01 g/100 g), and moisture (16.24 ± 0.003 g/100 g), respectively. Rhus natalensis showed the highest fiber content (9.54 ± 0.003 g/100 g). Mineral analysis showed that local wild fruits contained a considerable amount of minerals. The calcium concentration ranged from 99.51 mg/100 g in Euclea racemosa to 160.12 mg/100 g in Ficus sur. Potassium concentration varied from 54.34 mg/100 g in Euclea racemosa to 234 mg/100 g in Rhus vulgaris. Iron ranges from 21.4 mg/100 g in Rosa abyssinica to 41 mg/100 g in Rhus natalensis, and zinc ranges from 2.3 mg/100 g in Rhus vulgaris to 4.2 mg/100 g in Ficus sur. A high saponin content (2.12 mg/100 g) and a low tannin content (0.23 mg/100 g) were obtained in Rosa abyssinica. The phytate content (1.52 mg/100 g) and the oxalate content (0.9 mg/100 g) were high in Rhus natalensis. In conclusion, the present study shows that wild fruits can be used as food supplementation in food in a safe area.